Model characteristics of psychomotor and morphytological status of highly qualified female athletes - Belyakova, A. S.; Gorskaya, I. Y. (Uchenye zapiski universiteta imeni P.F. Lesgafta, 2019)
This article discusses the model of the athletic capabilities of the athletes involved in athletics, in particular, the model characteristics of the psychomotor and morphotypological status of highly qualified female athletes. Knowledge of the model characteristics of different indicators and signs of highly qualified athletes is necessary to increase the effectiveness of pedagogical control, adequate load planning, timely correction of the training process. The proposed model characteristics of the psychomotor and morphotypological status of highly qualified athletes can be used as a guide at the earlier stages of the long term sports training.